Про один із векторів херсонеської торгівлі - Котенко, В.В. (Археологія, 2017)
У статті розглянуто кераміку херсонеського виробництва, що походить з розкопок Тіри і вказує на північно-західний вектор торгівлі Херсонеса Таврійського в елліністичний час. The article analyzes a compact group of ceramics produced in Chersonesos from the excavations at Ancient Greek Tyras, which is stored in the collections of the Odesa Archaeological Museum of National Academy of Sciences of Ukraine. Established are the main forms of this type of wares: table jugs and a flask; they were widely known in Tauric Chersonesos and at the settlements of its chora in the North-Western Taurica. An ornamentation of these products is studied separately: horizontal encircling lines of red paint in the middle part of vessels and vegetative motifs, which can be stylistically attributed as a local imitation of Gadra style. The time of existence of such ware is referred to the Hellenistic period, mainly from the middle of the 4th to the 3rd centuries BC. These chronological frames coincide with the period of wide economic development of Tauric Chersonesos, when polis actively delivered goods to the settlements in North-Western Taurica, and also maintained trade contacts with Olbia. The analysis of ceramics from Tyras revealed the extent of northwestern vector of trade in Chersonesos and also added some information on goods exported from this polis. Статья посвящена анализу компактной группы керамики херсонесского производства, которая происходит из раскопок античной Тиры и хранится в фондах Одесского археологического музея НАН Украины. Установлены основные формы посуды данного типа — столовые кувшины и фляга, которые были широко известны в Херсонесе Таврическом и на поселениях его хоры в Северо-Западной Таврике. Отдельно рассмотрена орнаментация изделий — горизонтальные опоясывающие линии красной краской в средней части сосудов и растительные мотивы, которые стилистически можно отнести к местной имитации стиля Гадра. Время бытования такой посуды относится к эллинистическому периоду — преимущественно средина IV—ІII вв. до н. э. Эти хронологические рамки совпадают со временем бурного экономического развития Херсонеса Таврического, когда полис активно снабжал товарами поселения Северо-Западной Таврики, а также имел торговые контакты с Ольвией. Анализ керамики из Тиры показал протяженность северо-западного вектора херсонесской торговли, а также дополнил информацию о товарах, вывозимых из полиса.